Fault detection for power cable protection systems (pilot cable continuity testing and condition monitoring) - Eng, Jun Yee (Nanyang Technological University, 2023)
Protection systems are one of the most important systems in Electrical Grid Reliability. Differential Protection System is one of many protection systems currently being used worldwide. Pilot cables are the most important part of the Differential Protection System, as they transfer signals between the monitoring system and the isolating relays in the event of a fault. Pilot cables, just like all electrical cables, are susceptible to damage over many years. It is important to ensure that the cables are in working order and that all damaged wires in the Pilot cable can be identified and replaced as quickly as possible. This report presents the prototype of a product that can aid Power Engineers in identifying damaged wires in Pilot Cables, thus reducing the time taken to conduct continuity tests. This product involves using a LabVIEW Virtual Instrument (VI) in conjunction with an Arduino Uno Board.